Epigenetic modifications as novel therapeutic targets for Huntington's disease. (June 2014) - Wang, Fengli; Fischhaber, Paula L; Guo, Caixia; Tang, Tie-Shan
Huntington's disease is a late-onset, autosomal dominant neurodegenerative disorder characterized by motor, cognitive and psychiatric symptomatology. The earliest stage of Huntington's disease is marked by alterations in gene expression, which partially results from dysregulated epigenetic modifications. In past decades, altered epigenetic markers including histone modifications (acetylation, methylation, ubiquitylation and phosphorylation) and DNA modifications (cytosine methylation and hydroxymethylation) have been reported as important epigenetic features in patients and multiple animal models of Huntington's disease. Drugs aimed to correct some of those alterations have shown promise in treating Huntington's disease. This article discusses the field of epigenetics for potential Huntington's disease interventions and presents the most recent findings in this area.